Complement Inhibitors in Clinical Trials for Glomerular Diseases - Zipfel, Peter F.; Wiech, Thorsten; Rudnick, Ramona; Afonso, Sara; Person, Fermin; Skerka, Christine (Frontiers in Immunology, 2019)
Defective complement action is a cause of several human glomerular diseases including atypical hemolytic uremic syndrome (aHUS), anti neutrophil cytoplasmic antibody mediated vasculitis (ANCA), C3 glomerulopathy, IgA nephropathy, immune complex membranoproliferative glomerulonephritis, ischemic reperfusion injury, lupus nephritis, membranous nephropathy, and chronic transplant mediated glomerulopathy.Here we summarize ongoing clinical trials of complement inhibitors in nine glomerular diseases and show which inhibitors are used in trials for these renal disorders (http://clinicaltrials.gov)